Measuring Organizational Readiness for Implementing Change in Primary Care Facilities in Rural Bushbuckridge, South Africa - Hannah H. Leslie; Rebecca West; Rhian Twine; Nkosinathi Masilela; Wayne T. Steward; Kathleen Kahn; Sheri A. Lippman (Kerman University of Medical Sciences, 2022)
Meaningful gains in health outcomes require successful implementation of evidence-based interventions. Organizations such as health facilities must be ready to implement efficacious interventions, but tools to measure organizational readiness have rarely been validated outside of high-income settings. We conducted a pilot study of the organizational readiness to implement change (ORIC) measure in public primary care facilities serving Bushbuckridge Municipality in South Africa in early 2019. We administered the 10-item ORIC to 54 nurses and lay counsellors in 9 facilities to gauge readiness to implement the national Central Chronic Medicine Dispensing and Distribution (CCMDD) programme intended to declutter busy health facilities. We used exploratory factor analysis (EFA) to identify factor structure. We used Cronbach alpha and intraclass correlation (ICC) to assess reliability at the individual and facility levels. To assess validity, we drew on existing data from routine clinic monitoring and a 2018 quality assessment to test the correlation of ORIC with facility resources, value of CCMDD programme, and better programme uptake and service quality. Six items from the ORIC loaded onto a single factor with Cronbach's alpha of 0.82 and ICC of 0.23. While facility ORIC score was not correlated with implementation of CCMDD, higher scores were correlated with facility resources, perceived value of the CCMDD program, patient satisfaction with wait time, and greater linkage to care following positive HIV testing. The study is limited by measuring ORIC after programme implementation. The findings support the relevance of ORIC, but identify a need for greater adaptation and validation of the measure.